2022
DOI: 10.3390/nu14081550
|View full text |Cite
|
Sign up to set email alerts
|

Mediterranean Diet and Soy Isoflavones for Integrated Management of the Menopausal Metabolic Syndrome

Abstract: The transition from premenopause to postmenopause is associated with the development of multiple elements of Metabolic Syndrome (MetS) [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 25 publications
0
28
0
Order By: Relevance
“…Although limited to female participants, the estrogenic effects of isoflavones such as genistein may also have an effect. Genistein is known to reduce various risks, especially in postmenopausal females [ 58 , 59 , 60 ]. It is assumed that such risk reduction and improvement in quality of life may also affect mental stress.…”
Section: Discussionmentioning
confidence: 99%
“…Although limited to female participants, the estrogenic effects of isoflavones such as genistein may also have an effect. Genistein is known to reduce various risks, especially in postmenopausal females [ 58 , 59 , 60 ]. It is assumed that such risk reduction and improvement in quality of life may also affect mental stress.…”
Section: Discussionmentioning
confidence: 99%
“… 19 A clinical trial showed that genistein, which is the most abundant and active isoflavone in soy, acting as a natural selective ER-modulator, can improve surrogate endpoints associated with risk for diabetes and CVD in postmenopausal women with metabolic syndrome. 19 , 20 Most of the individuals with IFG studied by us were women of menopausal age, therefore, when planning further studies on the dietary prevention of T2D, it is advisable to study the effect of not only the use of dietary fibers, but also isoflavones. It is possible that the addition of soy products, such as tofu, may counteract the possible hormonal effects of dietary fiber.…”
Section: Discussionmentioning
confidence: 99%
“…The combined effects of lunasin and genistein can also be investigated in terms of diet. The combination of specific diets and bioactive compounds has been discussed to improve health benefits [ 115 ]. Investigating the lunasin chemopreventative and therapeutic effects together with the consumption of diets rich in isoflavones is an interesting alternative.…”
Section: Lunasin Products and Potential Combination Therapeuticsmentioning
confidence: 99%